2009
DOI: 10.1016/j.cpr.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding child sexual behavior problems: A developmental psychopathology framework

Abstract: Children exhibiting sexual behavior have increasingly gained the attention of child welfare and mental health systems, as well as the scientific community. While a heterogeneous group, children with sexual behavior problems consistently demonstrate a number of problems related to adjustment and overall development. In order to appropriately intervene with these children, a comprehensive understanding of etiology is imperative. The overarching goal of the present paper is to review the extant research on mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 122 publications
7
78
0
5
Order By: Relevance
“…Parents in our study seemed to experience slightly more feelings of shame and fewer feelings of distress related to the sexual abuse of their child compared to parents whose children completed trauma-focused cognitive behavioural therapy for different forms of trauma (Holt, Cohen, & Mannarino, 2015). In earlier studies, parental PTSD symptoms and psychopathology were found to be related to child PTSD symptoms, (sexual) behaviour problems, and lower parent–child relationship quality (Elkovitch, Latzman, Hansen, & Flood, 2009; Levendosky & Graham-Bermann, 2000; van Ee, Kleber, & Mooren, 2012). We found similar associations, except for sexual behaviour problems.…”
Section: Discussionmentioning
confidence: 97%
“…Parents in our study seemed to experience slightly more feelings of shame and fewer feelings of distress related to the sexual abuse of their child compared to parents whose children completed trauma-focused cognitive behavioural therapy for different forms of trauma (Holt, Cohen, & Mannarino, 2015). In earlier studies, parental PTSD symptoms and psychopathology were found to be related to child PTSD symptoms, (sexual) behaviour problems, and lower parent–child relationship quality (Elkovitch, Latzman, Hansen, & Flood, 2009; Levendosky & Graham-Bermann, 2000; van Ee, Kleber, & Mooren, 2012). We found similar associations, except for sexual behaviour problems.…”
Section: Discussionmentioning
confidence: 97%
“…With the exception of the study by Hackett, Carpenter, Patsios, and Eszter (2012) which suggested that interagency courses were effective in improving professionals' confidence in relation to reported levels of self-efficacy for working with young people with harmful sexual behaviours, there is a surprising lack of research focusing specifically on the extent of harmful sexual behaviours in the primary school environment and how they are managed (Elkovitch, Latzman, Hansen, & Flood, 2009). Similarly, there has been little evidence of work undertaken to address the needs of children who display harmful sexual behaviours (HM Probation, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Schools are a rich source of information about a child or young person's behaviour; outside the immediate family environment, schools are regarded as having one of the largest impacts on a child's development (Elkovitch et al, 2009). Teachers, in their daily interactions with students, are in a unique position to observe and identify sexualised behaviours that may cause concern.…”
Section: Introductionmentioning
confidence: 99%
“…These include self-stimulating behaviors (e.g., touching genitals in public/home), exhibitionism (e.g., exposing genitals to others), voyeurism (e.g., likes to watch others when they are exposed), and behaviors related to personal boundaries (e.g., standing too close to others) (Elkovitch, Latzman, Hansen, & Flood, 2009); sexual play between peers and siblings (e.g., playing doctor); and interest in sexual content in media (NCSBY, 2003). Conversely, infrequent sexual behaviors of children younger than 12 years of age include oral-genital contact, masturbating with an object, insertion of objects into the vagina or rectum, and intercourse (Friedrich, Grambsch, Broughton, Kuiper, & Beilke, 1991).…”
mentioning
confidence: 99%